Dari Hak Warga ke Rente Politik: Klientalisme Kewargaan dalam Proyek Penimbunan Jalan Beringin–Salati di Taliabu - Abd. Firman Bunta; Nurul Mawahda; Vanya Dyah Pitaloka Maharani A.C.R; Sabrina Nadia (Ideas Publishing, 2025)
The landfilling of the Beringin-Salati road in Taliabu exposes the practice of civic clientelism in infrastructure development. Rather than being the responsibility of the state, development is rife with rent-seeking exchanges between officials and contractors. This research aims to examine the patron-client relationship in the road project and the dilemma between citizen needs and fragile public legitimacy. Qualitative methods were used through case studies utilizing online media sources. The results indicate that road construction functions more as a means of distributing political patronage and strengthening patron-client networks than as a mechanism for fulfilling citizens' basic rights. The implications of this research enrich citizenship studies by highlighting the paradox of development in relation to weak policy governance at the local level.